Mathematic Model of Business-Ecosystem - O. E. Kalenov (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The article discusses the approach to building a mathematic model of business-ecosystem. To provide objectivity to the model it is proposed to study business-ecosystem as a customer-centric triad, which includes, firstly, the totality of elements of inter-branch belonging interacting in the process of development, production and marketing; secondly, one or several digital platforms with a set of various services integrated around one company. It gives the customer an opportunity to move in a ‘seamless’ way along them and obtain benefits from their complex use and satisfy his/her needs in conditions of one window. And thirdly, this pattern covers the organization itself, which uses innovation approaches to management and considers the enterprise as a self-developing complex living body that can effectively interact with the outward environment. The most important parameter showing profitability of staying in business-system is price of goods and services, which shall be studied from different sides at the same time: customer, supplier and organizer (proprietor) of the eco-system. Apart from profitable price for all participants, in order to assess efficiency of participation in business-ecosystems it is proposed to investigate functions of cost minimization, market share maximization and the rate of customer satisfaction maximization. The system of these criteria allows us, on the one hand, to identify limits of the business-ecosystem and on the other hand, to model the behavior of its elements and on this basis to make adequate managerial decisions.